Hadith #2132 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة (Sunan Abi Dawud)
A man called Basrah b. Akhtam married a woman. The narrator then reported the rest of the tradition to the same effect. This version added: And he separated them. The tradition narrated by Ibn Juraij is perfect.
Grade: Da'if

Hadith #3547 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not permissible for a woman to present a gift (from her husband’s property) except with the permission of her husband.
Grade: Hasan Sahih

Hadith #3933 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
On his father’s authority (this is AbulWalid’s version): A man emancipated a share in a slave and the matter was mentioned to the Prophet (ﷺ). He said: Allah has no partner. Ibn Kathir added in his version: The Prophet (ﷺ) allowed his emancipation.
Grade: Sahih

Hadith #3936 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
If anyone emancipates his share in a slave, he emancipates him (completely) by his property if he has property. The narrator Ibn al-Muthanna did not mention al-Nadr b. Anas. This is the version of Ibn Suwaid.
Grade: Sahih

Hadith #3937 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Ali bin al-Madini علي بن المديني; Bashayr bin Nahayk بشير بن نهيك السدوسي; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
If anyone emancipates a share in his slave, he should completely emancipate him if he has money; but if he has none, then slave will be required to work (to pay for his freedom), but he must not be overburdened.
Grade: Sahih